The Enhancement of Students Skill Aquisition Level at the Technical Colleges in Developing Countries Applying Dreyfus Model - Ohwojero Chamberlain (New Horizons in Education and Social Studies Vol. 8, 2021)
Achievement can be attained when skills acquired are well demonstrated during working process. Technical college students are equipped with good skills when Dreyfus model that is centred on procedural skill process was applied to train students, by pre-testing and post-testing the students at Sapele, Asaba, Agbor and Orgor technical colleges all in Southern part of Nigeria were the research was conducted. This paper is focused on how to train and enhance student’s skill level in technical colleges to improve man power. One research question was raised to guide the study and one hypothesis to check for level of significance at 0.05. An instrument titled ‘Bleeding Skill Task Performance’ was designed to collect data, through observation of students in the workshop. Data collected were analysed using compare mean, and analysis of covariance (ANCOVA) to check for level of significance. Findings were discussed and recommendations made to enhance student’s skill acquisition level. Based on these observations the researcher is encouraging and recommending to the Federal and State Government, Ministry of Education, Curriculum Planner, policy makers of educational programs in Nigeria to enforce the use and application of Dreyfus model of skill acquisition method in Nigerian technical colleges and every other institution of higher learning in Nigeria.